Az innovatív kis- és középvállalkozások finanszírozása kockázati tőkével: európai kihívások - Glavanits, Judit (Jelenkori Társadalmi és Gazdasági Folyamatok, 2012)
Closing the gap between the USA and EU venture capital market size is crutial for european innovative small and medium sized companies. As the financial crises started in 2008 weekend the possibilities for external capital, the role of venture capital financing is revaluated. The study analyses the similarities and differences in the legal rules of venture capital fund raising and financing revised by the USA's Dodd-Frank Act, and the European AIMF-directive. The study also suggest the changes in connection with the European Commission's prepared document on the European Venture Capital Fund, and it's effects on the innovative small-and medium sized companies. The conclusion is that the new rules of venture financing both in the USA and Europe sets up significantly more administrative difficulties for funds, but more stability and safe for entrepreneurs.